The Effects Of Teaching Method And Vocabulary Mastery Towards Students’ Speaking Skill At Private College In East Jakarta - WINDA WIDYANINGRUM (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2019)
ABSTRACT The purpose of this research is to know whether there are significant effects of Contextual Teaching and Learning Method and vocabulary mastery towards students’ speaking skill, both individually as well as simultaneously. The research was conducted at STKIP Kusuma Negara Jakarta Timur with the total sample 60 students that randomly taken. The method used in the research was a survey. Data vocabulary and speaking were acquired from the tests. The data was analyzed using Anova two ways. The result of the research concluded that there is no significant interaction contextual teaching and learning method and vocabulary mastery to student’s speaking skill. This is proven by the acquisition F0 = 0,161 and Sig = 0,689 > 0,05. Key words: Contextual Teaching and Learning Method, vocabulary mastery, speaking skill ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui pengaruh metode pembelajaran kontekstual dan penguasaan kosakata terhadap keterampilan berbicara siswa, baik secara individu maupun sebagai secara kelompok. Penelitian ini dilakukan di STKIP Kusuma Negara Jakarta Timur dengan total sampel 60 siswa yang diambil secara acak. Metode yang digunakan dalam penelitian adalah survei. Data untuk penguasaan kosakata dan keterampilan berbicara diperoleh dari tes. Data di analisis menggunakan Anova Dua Arah. Hasil penelitian menyimpulkan bahwa tidak terdapat pengaruh interaksi yang signifikan antara metode pembelajaran kontekstual dan penguasaan kosakata terhadap keterampilan berbicara siswa. Hal ini dibuktikan dengan perolehan F0 = 0,161 dan Sig = 0,689 > 0,05. Kata kunci: metode pembelajaran kontekstual, penguasaan kosakata, keterampilan berbicara